CT Hypoperfusion-Hypodensity Mismatch to Identify Patients With Acute Ischemic Stroke Within 4.5 Hours of Symptom Onset. (23rd November 2021) - Sporns, Peter B.; Kemmling, André; Minnerup, Heike; Meyer, Lennart; Krogias, Christos; Puetz, Volker; Thierfelder, Kolja; Duering, Marco; Kaiser, Daniel; Langner, Soenke; Massoth, Christina; Brehm, Alex; et al.
Abstract : Background and Objectives: To test the hypothesis that CT hypoperfusion-hypodensity mismatch identifies patients with ischemic stroke within 4.5 hours of symptom onset. Methods: We therefore performed the Retrospective Multicenter Hypoperfusion-Hypodensity Mismatch for The identification of Patients With Stroke Within 4.5 Hours study of patients with acute ischemic stroke and known time of symptom onset. The predictive values of hypoperfusion-hypodensity mismatch for the identification of patients with symptom onset within 4.5 hours were the main outcome measure. Results: Of 666 patients, 548 (82.3%) had multimodal CT within 4.5 hours and 118 (17.7%) beyond 4.5 hours. Hypoperfusion-hypodensity mismatch was visible in 516 (94.2%) patients with symptom onset within and in 30 (25.4%) patients beyond 4.5 hours. CT hypoperfusion-hypodensity mismatch identified patients within 4.5 hours of stroke onset with 94.2% (95% confidence interval [CI] 91.9%–95.8%) sensitivity, 74.6% (95% CI 66.0%–81.6%) specificity, 94.5% (95% CI 92.3%–96.1%) positive predictive value, and 73.3% (95% CI 64.8%–80.4%) negative predictive value. Interobserver agreement for hypoperfusion-hypodensity mismatch was substantial (κ = 0.61, 95% CI 0.53–0.69). Discussion: Patients with acute ischemic stroke with absence of a hypodensity on native CT (NCCT) within the hypoperfused core lesion on perfusion CT (hypoperfusion-hypodensity mismatch) are likely to be within the time window of thrombolysis. Applying this method may guide the decision to use thrombolysis in patients with unknown time of stroke onset. Trial Registration Information: ClinicalTrials.gov Identifier: NCT04277728. Classification of Evidence: This study provides Class III evidence that CT hypoperfusion-hypodensity mismatch identifies patients with stroke within 4.5 hours of onset.